Microbial biotransformation of estriol by the filamentous fungi - Masran, Nina Rosmarina (2016)
The main focus of our research was to observe the biological transformation of steroidal compounds using filamentous fungi. The steroidal compound estriol was inoculated into filamentous fungal Trichothecium Roseum cultures. In order to achieve the objective, the large scale production of secondary metabolites has been used to identify any potential and abundant metabolites of estriol. Time course study of fermentation of estriol with filamentous fungus was carried out. The transformed products of estriol have been investigated through TLC and HPLC method. We have found that the Trichothecium Roseum produced maximum amount of secondary metabolite after 9 days of incubation with estriol. After analysis of metabolite profiling by TLC and HPLC, there are few possible secondary metabolite of fungi discovered. Due to the time limitation, the separation and characterization of metabolites have not been performed.